CS-Bot: Smart and Interactive Digital Innovation as a Modern Solution for Early Detection of Stunting - Andesti, Cyntia Lasmi; Dian, Rahmad; Ningsih, Sri Restu (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
The high prevalence of stunting in West Sumatra Province, especially in Pariaman City, is a big challenge in efforts to improve children's health. With more than 600 children at high risk of stunting, manual approaches in examining and recording health data are less effective. This system not only slows down the detection process but also has the potential to result in data loss and redundancy. In this context, late detection hinders early prevention, which is especially important in the First 1000 Days of Life (HPK) period. Therefore, this research aims to develop a chatbot-based application that is able to detect stunting quickly and accurately. This application is named CS-Bot, namely Prevent Stunting using Chatbot. This application is designed to be easy for the public to use, while providing education about the importance of stunting prevention. Research methods include analysis of data on factors and symptoms of stunting, formation of rules using the Forward Chaining Method, and probability calculations using Certainty Factor. The data used in this study comes from health centers and some data comes from several experts who are accustomed to dealing with stunting problems in children. It is hoped that the research results will not only provide tools for parents and the community, but will also become the basis for making more effective policies in stunting prevention programs in Indonesia, especially in West Sumatra.